All Days 2013
DOI: 10.2118/165552-ms
|View full text |Cite
|
Sign up to set email alerts
|

Specifics and Challenges of Heavy oil Production in Northen Siberia Illustration Based on Biggest Heavy Oil Project in Russia

Abstract: Russkoye heavy oil field is located in the northern part of Siberia. The field was discovered in 1968. It is characterized by the huge reserves: more than 1.3 billion tonn of oil in place and remote location (the field is located to the north from the polar circle). Main challenges for the field development are: unconsolidated formation, gas cap, high heterogeneity of formation, permafrost zone and heavy oil. This paper covers latest experience (2007)(2008)(2009)(2010)(2011)(2012) obtained during field develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Thus, a flowmeter with a radioactive source provides good resolution for flow measurements for all phases of the measured fluid. In Russia, multiphase flow metering is used in both gas condensate wells and high-viscosity oil fields (Aksenov, 2013).…”
Section: Figure 3-gas Lift Well Surveys Using Group Metering Unitmentioning
confidence: 99%
“…Thus, a flowmeter with a radioactive source provides good resolution for flow measurements for all phases of the measured fluid. In Russia, multiphase flow metering is used in both gas condensate wells and high-viscosity oil fields (Aksenov, 2013).…”
Section: Figure 3-gas Lift Well Surveys Using Group Metering Unitmentioning
confidence: 99%
“…In addition, it was observed that maximum recovery could be achieved by keeping injection rates as low as possible. Vologodskiy et al performed studies on the Russkoye oil field in Russia with 1.3 billion ton of oil in place. Besides the high oil density and viscosity found in this field, development process was complicated by the high heterogeneity of the formation.…”
Section: Introductionmentioning
confidence: 99%